Inspiring desirability or ensuring feasibility: Destination image and psychological distance - Wang, Fei; Feng, Yu; Wang, Zuo‐Jun (The international journal of tourism research, 2022)
Destination image plays a pivotal role in shaping the judgment of tourists. However, limited information is available on how tourists respond to various destination images. By using single‐factor between‐subject design, study 1 confirmed that cognitive image causes tourists to judge the destination in near‐psychological distance and that affective image causes them to judge the destination in far psychological distance. By using single‐factor and two‐factor between‐subject design separately, studies 2 and 3 further confirmed that a match between destination image and psychological distance of the tourists has a positive effect on the attractiveness and persuasiveness judgment toward the destination advertisement. 旅游地形象在塑造游客对旅游地的判断和意图中起到关键作用。然而，很少有研究探讨游客在面临不同旅游地形象时所做出的差异化反应。本研究从构念水平理论视角出发，探讨认知型形象和情感型形象如何影响潜在消费者的判断。实验1采用单因素被试间实验设计发现，认知型形象令游客认为旅游地的心理距离比较近，而情感型形象令游客认为旅游地的心理距离比较远。实验2和实验3分别使用单因素和双因素被试间设计发现，旅游地形象和游客的心理距离相匹配对于旅游地广告的说服力和吸引力判断有积极影响。本研究建议旅游地管理者应考虑将广告与游客的心理距离相匹配，以增加旅游地形象的吸引力和说服力。